Soybean for Human Consumption and Animal Feed - Sudarić, Aleksandra (IntechOpen, 2020)
Soybean is the main oilseed crop worldwide, a staple crop for protein-rich food and feed as well as a significant source of nutraceutical compounds with many different medical benefits. Soybean for Human Consumption and Animal Feed highlights the state of research in soybean nutritional attributes as well as science-based approaches defining the future of soybean for human consumption and animal feed. Over seven chapters, this book presents a comprehensive picture of the potential of soybean for human and animal diets and health as well as quality stock for pharmaceutical and functional food industries with an emphasis on the importance of genetic improvement of soybean germplasm in enhancing healthy and safe properties of final soy products.